DAMPAK GLOBALISASI TERHADAP PERUBAHAN SOSIAL EKONOMI DI WILAYAH PESISIR: STUDI KOMUNITAS NELAYAN TRADISIONAL TUBAN - Inarotul A’yun (LPPM STAI Muhammadiyah Probolinggo, 2026)
Globalization is a multidimensional phenomenon that has brought significant impacts on the social, economic, and ecological life of coastal communities, particularly traditional fishing communities. This study aims to analyze the impact of globalization on changes in the socio-economic structure of traditional fishermen in the coastal areas of Tuban Regency, as well as to identify adaptation and empowerment strategies that can enhance their competitiveness and welfare. This research employs a qualitative approach with a case study design, conducted in five coastal districts of Tuban Regency. Data were collected through participatory observation, in-depth interviews, Focus Group Discussions (FGDs), and documentation, involving traditional fishermen and relevant stakeholders as key informants. Data analysis was carried out interactively through data reduction, data display, and conclusion drawing, and was strengthened by source and method triangulation. The findings indicate that globalization has intensified economic inequality between traditional and modern fishermen due to disparities in access to technology, capital, and markets. In addition, changes in the social structure were identified, characterized by the weakening of mutual cooperation values, increasing individualism, and shifts in work patterns and social relations within fishing communities. From an ecological perspective, globalization-driven pressures have contributed to the overexploitation of marine resources, adversely affecting the sustainability of traditional fishermen’s livelihoods. This study highlights the importance of fisherman empowerment strategies based on strengthening local capacities, policy protection, and sustainable marine resource management, in line with the achievement of the Sustainable Development Goals (SDGs). The findings are expected to serve as an academic reference and policy recommendation for inclusive and sustainable coastal development.